2017
DOI: 10.1523/jneurosci.2738-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Stress Response in Hypoxia-Induced Diffuse White Matter Injury

Abstract: Currently no treatments exist for preterm infants with diffuse white matter injury (DWMI) caused by hypoxia. Due to the improved care of preterm neonates and increased recognition by advanced imaging techniques, the prevalence of DWMI is increasing. A better understanding of the pathophysiology of DWMI is therefore of critical importance. The integrated stress response (ISR), a conserved eukaryotic response to myriad stressors including hypoxia, may play a role in hypoxia-induced DWMI and may represent a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…MCH is a well described model of Diffuse White Matter Injury (DWMI) (Clayton et al, 2017a; Clayton et al, 2017b; Fancy et al, 2011; Scafidi et al, 2014; Yuen et al, 2014) and protein samples were generously provided by Brian Popko. In brief, postnatal day 3 (P3) C57Bl6 pups were placed into a BioSpherix chamber maintained at 10+/- 0.5% O2 by displacement of nitrogen until P11.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCH is a well described model of Diffuse White Matter Injury (DWMI) (Clayton et al, 2017a; Clayton et al, 2017b; Fancy et al, 2011; Scafidi et al, 2014; Yuen et al, 2014) and protein samples were generously provided by Brian Popko. In brief, postnatal day 3 (P3) C57Bl6 pups were placed into a BioSpherix chamber maintained at 10+/- 0.5% O2 by displacement of nitrogen until P11.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, postnatal day 3 (P3) C57Bl6 pups were placed into a BioSpherix chamber maintained at 10+/- 0.5% O2 by displacement of nitrogen until P11. Animals were then quickly sacrificed by CO 2 asphyxiation followed by decapitation and the frontal cortex was isolated as this region has been shown to contain subcortical white matter that is susceptible to hypoxia-induced DWMI (Clayton et al, 2017b; Jablonska et al, 2012; Sanjana et al, 2014; Yuen et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue from mild chronic hypoxia (MCH) mice MCH is a well described model of Diffuse White Matter Injury (DWMI) (Clayton et al, 2017a(Clayton et al, , 2017bFancy et al, 2011;Scafidi et al, 2014;Yuen et al, 2014) and protein samples were generously provided by Brian Popko. In brief, postnatal day 3 (P3) C57Bl6 pups were placed into a BioSpherix chamber maintained at 10+/À 0.5% O2 by displacement of nitrogen until P11.…”
Section: Human Oligocortical Spheroid Productionmentioning
confidence: 99%
“…We established the preterm PVL model by placing mice in severe acute hypoxia or room air conditions, according to the methods described by Clayton et al with brief modification ( 33 ). It was observed that reduced myelination due to a disrupted oligodendrocyte progenitor (preOL) pool contributes to PVL.…”
Section: Resultsmentioning
confidence: 99%
“…All the male pups were randomly divided into three groups: the normoxia group (Control), the hypoxia-induced saline-treated group (Hypoxia), and the hypoxia-induced IL-4-treated group (Hypoxia + IL-4 group). The PVL animal model was established according to Clayton et al and Shen et al with modification ( 33 , 34 ). Given the unstable state of C57BL/6 mice under hypoxic environments, all the male pups were fostered to gestational age-matched lactating CD1 (ICR) dams at postnatal day 1 (P1).…”
Section: Methodsmentioning
confidence: 99%